Streamlines based visualization of air flow in clouds - Kovačević Marko M.; Mihajlović Vladan T.; Rančić Dejan D. (Serbian Journal of Electrical Engineering, 2012)
The most important functionality of the hail suppression information system in Serbia is to enable timely and reliable detection of the formation of hail-containing clouds. Improvement of this functionality can be achieved by adequate visualization of air flow (wind) inside the cloud system. This was the motivation for implementing a 2D steady vector field visualization method, based on the streamlines method. The choice of this method is dictated by the requirements for the given appliance: efficiency (a crucial requirement in hail suppression systems), generality of use, an accurate and easily understandable display. By implementing algorithms for streamlines seeding strategy and streamlines points distance control, the infinite loop problem that occurs due to the existence of field vortices is eliminated and evenly spaced streamlines are obtained. For analyzing the influence of the implemented method’s parameters on performance and image quality, a framework for visualization is developed. The implemented method is successfully applied for visualization of data obtained from meteorological radars.